Hubungan Komunikasi Guru dengan Minat Belajar Siswa: (Studi di MTs Al-Inayah) - Ela Kusmawati, Rafiudin (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2019)
The teacher is an educator who teaches students in the class whose job is to convey the material and guide their students in the teaching and learning process in the classroom. The teaching process that occurs in the classroom is a process of communication between the teacher and students. The role of the teacher is very important in education to determine the success or failure of the students they teach, therefore communication between the teacher and students in the class needs to be considered. This paper reviews quantitatively the relationship between teacher communication and student learning interest. Is better communication between teacher and student can increase student learning interest? With descriptive-analytical methods accurate data in the field about 116 conditions with a sample size of 25% is 29 respondents. Statistical data shows that there is a significant relationship and is included in the moderate/sufficient category. This is evident from the results of the calculation of variable X obtained mean = 66 Median = 66.59 Mode = 66.49, for variable Y classified as moderate/sufficient, as evidenced by the analysis of central tendency obtained by the central obtained Mean = 63 Median = 64 Mode = 67.47, thus, the Relationship of Teachers' Communication to Student Learning Interests in the Study of Moral Law is significant.